Skip Navigation

Quadratic Formula

Solve quadratic equations using the formula

Atoms Practice
Estimated17 minsto complete
Practice Quadratic Formula
This indicates how strong in your memory this concept is
Estimated17 minsto complete
Practice Now
Turn In
Quadratic Formula

What if you needed to solve the quadratic equation \begin{align*}x^2+x-5=0\end{align*} in order to determine the width of a rectangular map? You graphed the function \begin{align*}f(x)=x^2+x-5\end{align*}, but from the graph you can only tell the approximate width, and you want a more precise answer. In this Concept, you'll learn to use the quadratic formula to solve quadratic equations like the one representing this situation so that you can get exact solutions to the equations.


Previous Concepts have presented three methods to solve a quadratic equation:

  • By graphing to find the zeros;
  • By solving using square roots; and
  • By using completing the square to find the solutions

This Concept will present a fourth way to solve a quadratic equation: using the quadratic formula.

History of the Quadratic Formula

As early as 1200 BC, people were interested in solving quadratic equations. The Babylonians solved simultaneous equations involving quadratics. In 628 AD, Brahmagupta, an Indian mathematician, gave the first explicit formula to solve a quadratic equation. The quadratic formula was written as it is today by the Arabic mathematician Al-Khwarizmi. It is his name upon which the word “Algebra” is based.

The solution to any quadratic equation in standard form, \begin{align*}0=ax^2+bx+c\end{align*}, is:

\begin{align*}x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}\end{align*}

Example A

Solve \begin{align*}x^2+10x+9=0\end{align*} using the quadratic formula.


We know from the last Concept the answers are \begin{align*}x=-1\end{align*} or \begin{align*}x=-9\end{align*}.

By applying the quadratic formula and \begin{align*}a=1, b=10\end{align*}, and \begin{align*}c=9\end{align*}, we get:

\begin{align*}x &= \frac{-10 \pm \sqrt{(10)^2-4(1)(9)}}{2(1)}\\ x &= \frac{-10 \pm \sqrt{100-36}}{2}\\ x &= \frac{-10 \pm \sqrt{64}}{2}\\ x &= \frac{-10 \pm 8}{2}\\ x &= \frac{-10 + 8}{2} \ or \ x=\frac{-10-8}{2}\\ x &= -1 \ or \ x=-9\end{align*}

Example B

Solve \begin{align*}-4x^2+x+1=0\end{align*} using the quadratic formula.


\begin{align*}\text{Quadratic formula:} && x & =\frac{-b \pm \sqrt{b^2-4ac}}{2a}\\ \text{Plug in the values} \ a=-4, b=1, c=1: && x& =\frac{-1 \pm \sqrt{(1)^2-4(-4)(1)}}{2(-4)}\\ \text{Simplify:} && x & =\frac{-1 \pm \sqrt{1+16}}{-8}=\frac{-1 \pm \sqrt{17}}{-8}\\ \text{Separate the two options:} && x&=\frac{-1+\sqrt{17}}{-8} \ \text{and} \ x=\frac{-1-\sqrt{17}}{-8}\\ \text{Solve:} && x & \approx -.39 \ \text{and} \ x \approx .64\end{align*}

Example C

Solve \begin{align*}8t^2+10t+3=0\end{align*} using the quadratic formula.


\begin{align*}\text{Quadratic formula:} && x & =\frac{-b \pm \sqrt{b^2-4ac}}{2a}\\ \text{Plug in the values} \ a=8, b=10, c=3: && x& =\frac{-10 \pm \sqrt{(10)^2-4(8)(3)}}{2(8)}\\ \text{Simplify:} && x & =\frac{-10 \pm \sqrt{100+96}}{16}=\frac{-10 \pm \sqrt{196}}{16}\\ \text{Separate the two options:} && x&=\frac{-10+\sqrt{196}}{16} \ \text{and} \ x=\frac{-10-\sqrt{196}}{16}\\ \text{Separate the two options:} && x&=\frac{-10+14}{16} \ \text{and} \ x=\frac{-10-14}{16}\\ \text{Solve:} && x & =\frac{1}{4} \ \text{and} \ x =-\frac{3}{2}\end{align*}

Guided Practice

Solve \begin{align*}3k^2+11k=4\end{align*} using the quadratic formula.


First, we must make it so one side is equal to zero:

\begin{align*}3k^2+11k=4 \Rightarrow 3k^2+11k-4=0\end{align*}

Now it is in the correct form for using the quadratic formula.

\begin{align*}\text{Quadratic formula:} && x & =\frac{-b \pm \sqrt{b^2-4ac}}{2a}\\ \text{Plug in the values} \ a=3, b=11, c=-4: && x& =\frac{-11 \pm \sqrt{(11)^2-4(3)(-4)}}{2(3)}\\ \text{Simplify:} && x & =\frac{-11 \pm \sqrt{121+48}}{6}=\frac{-11 \pm \sqrt{169}}{6}\\ \text{Separate the two options:} && x&=\frac{-11+\sqrt{169}}{6} \ \text{and} \ x=\frac{-11-\sqrt{169}}{6}\\ \text{Separate the two options:} && x&=\frac{-11+13}{6} \ \text{and} \ x=\frac{-11-13}{6}\\ \text{Solve:} && x & =\frac{1}{3} \ \text{and} \ x =-4\end{align*}

  1. What is the quadratic formula? When is the most appropriate situation to use this formula?
  2. When was the first known solution of a quadratic equation recorded?

Solve the following quadratic equations using the quadratic formula.

  1. \begin{align*}x^2+4x-21=0\end{align*}
  2. \begin{align*}x^2-6x=12\end{align*}
  3. \begin{align*}3x^2-\frac{1}{2}x=\frac{3}{8}\end{align*}
  4. \begin{align*}2x^2+x-3=0\end{align*}
  5. \begin{align*}-x^2-7x+12=0\end{align*}
  6. \begin{align*}-3x^2+5x=0\end{align*}
  7. \begin{align*}4x^2=0\end{align*}
  8. \begin{align*}x^2+2x+6=0\end{align*}

Khan Academy


Notes/Highlights Having trouble? Report an issue.

Color Highlighted Text Notes
Show More

Image Attributions

Explore More

Sign in to explore more, including practice questions and solutions for Quadratic Formula.
Please wait...
Please wait...